2016
DOI: 10.1002/mame.201600139
|View full text |Cite
|
Sign up to set email alerts
|

Near‐Infrared Light Triggered Soft Actuators in Aqueous Media Prepared from Shape‐Memory Polymer Composites

Abstract: Light triggered soft actuator in aqueous media has applications in operating underwater objects, creating liquid flow, and adjusting reaction velocity, etc. Here, composites prepared from commercial materials, poly[ethylene‐ran‐(vinyl acetate)] (EVA) and aniline black (AB), are reported as one cost efficient material for preparing such actuator, where EVA and AB work respectively as shape‐memory polymer matrix and near‐infrared light triggered photothermal filler. Upon irradiation, the temperature of the compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 34 publications
2
9
0
Order By: Relevance
“…As shown in Figure b, photothermal efficiency which is defined as the slope value by fitting the relation between the balanced temperature and PD in a linear manner no longer increased after introducing 0.2 phr AB. The similar result was also observed in EVA/AB composite system, where a high amount of 2 phr AB was required to retard the further increase in photothermal effect due to the worse dispersion …”
Section: Resultssupporting
confidence: 76%
See 1 more Smart Citation
“…As shown in Figure b, photothermal efficiency which is defined as the slope value by fitting the relation between the balanced temperature and PD in a linear manner no longer increased after introducing 0.2 phr AB. The similar result was also observed in EVA/AB composite system, where a high amount of 2 phr AB was required to retard the further increase in photothermal effect due to the worse dispersion …”
Section: Resultssupporting
confidence: 76%
“…In comparison, large aggregates of carbon black with the same loading existed in the same epoxy coatings (Figure c). Besides, as reported previously, large AB aggregates were observed in another polymer system of poly[ethylene‐ ran ‐(vinyl acetate)] (EVA) . The comparison among such three systems indicates the unique well dispersion of AB in epoxy coatings.…”
Section: Resultssupporting
confidence: 74%
“…Their experimental research showed that the flexible gripper made by SMPAs could grasp a variety of irregular or fragile objects, and could achieve high-precision control. Fang et al [11] mixed ethylene-vinyl acetate and aniline black to provide one candidate material for near-infrared light triggered flexible actuator in aqueous media, and demonstrated the SMPA made by this new material was capable of opening and closing the arms reversibly via periodic variation in irradiation PD successfully. SMPA is suitable for small volume, simple in structure, easy to control, and strong adaptability to the environment [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Shape memory actuators are another type of soft actuators that have been developed by researchers [14], [15]. A shapememory alloy (SMA) is an alloy that can be deformed when cold but returns to its pre-deformed ("remembered") shape when heated.…”
Section: Introductionmentioning
confidence: 99%